Network-Coding-Based Cooperative ARQ Medium Access Control Protocol for Wireless Sensor Networks. (4th December 2011) - Antonopoulos, Angelos; Verikoukis, Christos
Abstract : We introduce a novel Medium Access Control (MAC) protocol for Automatic Repeat reQuest-based (ARQ-based) cooperative wireless sensor networks. Using network coding techniques, we achieve a better network performance in terms of energy efficiency without compromising the offered Quality of Service (QoS). The proposed solution is compared to other cooperative schemes, while analytical and simulation results are provided to evaluate our protocol.